Umpiring security Models for MANETS - Kathirvel, Ayyaswamy (2012)
In wireless mobile ad hoc networks, packet delivery is achieved through two closely related network-layer operations: ad hoc routing and packet forwarding. As a result any security solution should encompass the protection of both. Protecting the network layer operations such as routing the control messages and data packet forwarding, from malicious attacks is an important and challenging issue in both wired and wireless mobile networks and the issue becomes even more challenging in the case of wireless mobile ad hoc network. Malicious nodes may disrupt routing algorithms by transmitting a false hop count; by dropping data packets and by routing the packets through unintended routes and so on. The work presented in this thesis attempts to improve the performance of wireless mobile ad hoc networks by protecting the network layer. Five studies are presented.